PI3K/AKT/mTOR pathway inhibitors inhibit the growth of melanoma cells with mTOR H2189Y mutations in vitro. Issue 7 (3rd July 2018) - Wu, Xiaowen; Yu, Jiayi; Yan, Junya; Dai, Jie; Si, Lu; Chi, Zhihong; Sheng, Xinan; Cui, Chuanliang; Ma, Meng; Tang, Huan; Xu, Tianxiao; Yu, Huan; et al.
ABSTRACT: mTOR is an important therapeutic target in many types of cancers. In melanoma, the mTOR nonsynonymous mutation rate is up to 10.4%. However, mTOR inhibitors have shown limited effects in clinical trials of melanoma. Because mTOR mutations are distributed, not selecting patients with specific mTOR mutations may be the main reason for therapeutic failures. Our previous research found that mutations in the mTOR P2213S and S2215Y kinase domains resulted in gain-of-function and were sensitive to specific inhibitors. The purpose of this study was to test the effect of heterozygous/homozygous H2189Y mutations on downstream pathways and sensitivity to inhibitors. mTOR kinase activity was analyzed by western blot and a K-LISA™ mTOR activity kit. The sensitivity of melanoma cells to inhibitors was tested by a proliferation assay. The expression of downstream pathway proteins was also analyzed by western blot. The results showed that heterozygous/homozygous H2189Y mutations were gain-of-function. The heterozygous H2189Y mutation was sensitive to the AKT inhibitor, AZD5363, and the phosphoinositide 3-kinase inhibitor, LY294002. The homozygous H2189Y mutation was sensitive to the mTOR inhibitor, everolimus, and the AKT inhibitors AZD5363 and MK-2206 2HCL, and the phosphoinositide 3-kinase inhibitor, LY294002. These results indicated that homozygous mutations in the kinase domain have a greater effect on protein function than heterozygous mutations. The mTOR kinase domain may play an important role in mTOR kinase activity and may be the target of selective inhibitors. Our study can facilitate the selection of appropriate inhibitors for patients in clinical trials.